THE EFFECT OF CIRCUIT LEARNING MODEL ON SOCIAL STUDIES LEARNING OUTCOMES OF POST-PANDEMIC STUDENTS - Wanhar, Fira Astika; Nazaruddin, Ilham (Teunuleh Publisher, 2022)
This study aims to determine the differences in student learning outcomes who are taught using the circuit learning model compared to the conventional learning model. This type of research is an experimental one. This research was conducted at SD Swasta 10 PAB Sampali with a sample of 40 students. The research instrument is in the form of multiplechoice learning outcomes test. The data analysis technique used T test. The results showed that the social studies learning outcomes of students who were taught using the circuit learning model were higher than those of the conventional learning model. Based on the results of the study, it was concluded that the use of the Circuit Learning model was suitable for use in the social studies learning process.